Development of performance characterization in VSI fed induction motor drives using random PWM - Mohan Das Raman; Chandirasekaran Easwaran; Vinod Kumar Srinivasan; Bharatiraja Chockalingam (Institute of Advanced Engineering and Science, 2022)
Any industrial or power sector application requires a pulse width modulation (PWM) inverter. Industrial drives in particular are highly concerned with industrial standards. To satisfy the voltage source inverter (VSI) drives objects, a variety of PWM approaches are used, including inverter DC input voltage utilizations, suppression of higher and lower order of harmonics, as well as spreading harmonics, acoustic noise reduction, among others PWMs. One of the better approaches for minimizing noise on voltage source threephase inverter fed drives is random pulse width modulation PWM random palse width modulation (RPWM). Despite the fact that these described RPWM approaches are superior in terms of harmonic spreading and mitigation, these methods are unable to achieve the target DC-link utilizations. As a result, the focus of this paper is on combining multicarrier RPWM principles with space vector PWM space vector pulse width modulation (SVPWM) to produce multi-carrier random SVPWM (MCRSVPWM). The suggested PWM generates random unsystematic triangle carrier (5 kHz, 2.5 kHz, 1.25 kHz, 1 kHz) based pulses, whereas the traditional random PWM techniques are uses a fixed frequency triangular carrier to generate random pulse positions. Asynchronous induction motor driving simulation is carried out using MATLAB/Simulink. The proposed MCRSVPWM is put to the test with a 2kW six-switch VSI-fed induction motor drive system.